2012
DOI: 10.1002/adfm.201200052
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Design of Protein Nanomaterials for Hydrophobic Molecular Transport

Abstract: Biomaterials such as self-assembling biological complexes have demonstrated a variety of applications in materials science and nanotechnology. The functionality of protein-based materials, however, is often limited by the absence or locations of specific chemical conjugation sites. In this investigation, we developed a new strategy for loading organic molecules into the hollow cavity of a protein nanoparticle that relies only on non-covalent interactions, and we demonstrated its applicability in drug delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 69 publications
2
58
1
Order By: Relevance
“…121 Hydrophobic drug molecules, peptides, and gene drugs are covalently conjugated to the hollow cavity of the protein scaffold or noncovalently loaded into the internal space. [122][123][124][125] Generally, restricted by the number of attachment sites, most of the protein NP-based nanomedicines prepared by conventional chemical conjugation present the same drawback of lower drug-loading content (,10%). 122 One feasible way to enhance the drug-loading capacity of protein nanocarriers is designing and increasing the hydrophobic surface area of the protein NP.…”
Section: Protein Nps As Carriersmentioning
confidence: 99%
“…121 Hydrophobic drug molecules, peptides, and gene drugs are covalently conjugated to the hollow cavity of the protein scaffold or noncovalently loaded into the internal space. [122][123][124][125] Generally, restricted by the number of attachment sites, most of the protein NP-based nanomedicines prepared by conventional chemical conjugation present the same drawback of lower drug-loading content (,10%). 122 One feasible way to enhance the drug-loading capacity of protein nanocarriers is designing and increasing the hydrophobic surface area of the protein NP.…”
Section: Protein Nps As Carriersmentioning
confidence: 99%
“…The improvements in tuning hydrogel features in terms of chemical and physical properties led to the recent fabrication of 3D scaffolds with tailored morphological and functional properties able to variously reproduce the basic requirements (i.e., biological recognition, molecular transport) to mimic natural tissue functions . Here, we have fabricated macroporous PEGDA hydrogels by the combination of UV photopolymerization and salt leaching technique, also improving the bioactivity of pore surface via premineralization treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in tuning hydrogel features in terms of chemical and physical properties led to the recent fabrication of 3D scaffolds with tailored morphological and functional properties able to variously reproduce the basic requirements (i.e., biological recognition, molecular transport) to mimic natural tissue functions. [38][39][40] Here, we have fabricated macroporous PEGDA hydrogels by the combination of UV photopolymerization and salt leaching technique, also improving the bioactivity of pore surface via premineralization treatment. First, water soluble porogens-NaCl crystals from 300 to 500 mm in size-allows generating pores within a range of 100-400 mm, able to promote cell adhesion and proliferation in bone regeneration as just discussed in previous studies on similar systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al showed that the E2 protein can be modified both on the internal and external surfaces for loading of drug molecules inside and for displaying functional epitopes on the outer surface of the nanocage simultaneously. 21 Thus, the E2 protein cage offers promising avenues for tailored engineering of the exterior, the subunit-subunit interfaces and the interior to produce the desired modifications. 22 Vaults.…”
Section: Engineered Protein Cages In Biomedical Applicationsmentioning
confidence: 99%